Youths' Knowledge About Risk Factors That Contribute To Violence - Kareem Ghadhban Sajem (Kufa Journal for Nursing Sciences)
Objectives: The study aims to identify youths' knowledge about risk factors that contribute in violence and statistical differences between demographic data of youths regarding to their knowledge and sources of such knowledge.